2013
DOI: 10.1103/physrevlett.110.177404
|View full text |Cite
|
Sign up to set email alerts
|

Optical Emission of a Strained Direct-Band-Gap Ge Quantum Well Embedded Inside InGaAs Alloy Layers

Abstract: Type of publicationArticle (peer-reviewed) Access to the full text of the published version may require a subscription. Rights

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 39 publications
4
50
0
1
Order By: Relevance
“…The resulting ultrahigh mobilities make highly-strained Ge a very exciting candidate for CMOS channels and ultra-fast MOSFETs within the established Si-fabrication technology processes. Since the strains at which this is predicted to occur have already been demonstrated [7][8][9] in nanostructures, these extraordinary increases in mobility are well within the reach of the current technology.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The resulting ultrahigh mobilities make highly-strained Ge a very exciting candidate for CMOS channels and ultra-fast MOSFETs within the established Si-fabrication technology processes. Since the strains at which this is predicted to occur have already been demonstrated [7][8][9] in nanostructures, these extraordinary increases in mobility are well within the reach of the current technology.…”
Section: Discussionmentioning
confidence: 82%
“…This strain has been achieved by growing a narrow strip of Ge on a (001) In x Ga 1Àx As alloy substrate. 7,25,26 The supplementary information of Ref. 6 (see reference within), and Ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The boundary conditions were given by the experimental values of the band gap and effective masses of InGaAs and the calculated band offsets from Ref. [23]. We used the boundary matching conditions from Harrison [24].…”
Section: Theoretical Model Of Strained Gementioning
confidence: 99%
“…It is known that mechanical strain and nanostructuring change the energy band structure of semiconductor materials [1][2][3][4][5]. Thus, the authors of [6] reported that their photoconductivity measurements provide exper imental evidence of a reduction of the band gap in ten sile strained silicon to 0.59 eV.…”
mentioning
confidence: 97%